Transcriptomic landscape of Pueraria lobata demonstrates potential for phytochemical study - Han, Rongchun; Takahashi, Hiroki; Nakamura, Michimi; Yoshimoto, Naoko; Suzuki, Hideyuki; Shibata, Daisuke; Yamazaki, Mami; Saito, Kazuki (Frontiers in Plant Science, 2015)
Pueraria lobata (Willd.) Ohwi has a long and broad application in the treatment of disease. However, in the US and EU, it is treated as a notorious weed. The information to be gained from decoding the deep transcriptome profile would facilitate further research on P. lobata. In this study, more than 93 million fastq format reads were generated by Illumina’s next-generation sequencing approach using five types of P. lobata tissue, followed by CLC de novo assembly methods, ultimately yielding about 83,041 contigs in total. Then BLASTx similarity searches against the NCBI NR database and UniProtKB database were conducted. Once the duplicates among BLASTx hits were eliminated, ID mapping against the UniProt database was conducted online to retrieve Gene Ontology information. In search of the putative genes relevant to essential biosynthesis pathways, all 1,348 unique enzyme commission numbers were used to map pathways against the Kyoto Encyclopedia of Genes and Genomes. Enzymes related to the isoflavonoid and flavonoid biosynthesis pathways were focused for detailed investigation and subsequently, qRT-PCR was conducted for biological validation. Metabolites of interest, puerarin and daidzin were studied by HPLC. The findings in this report may serve as a footstone for further research into this promising medicinal plant.